2017
DOI: 10.1007/s10068-017-0185-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of anchovy by-product protein coating incorporated with thyme essential oil on the shelf life of anchovy (Engraulis encrasicolus L.) fillets

Abstract: The effects of anchovy by-product protein coatings incorporated with thyme essential oil (TEO) on the shelf life of anchovy ( L.) fillets stored at 4 ± 1 °C were investigated. We grouped fillets in three categories: untreated fillets, fillets treated in coating solution alone, and fillets treated in coating solution containing 1.5% TEO and analyzed on 0, 3, 6, and 9 days of storage. It was observed that the total volatile basic nitrogen (TVB-N) and pH of all the fillet groups increased under cold storage condi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 32 publications
0
5
0
1
Order By: Relevance
“…Six condiments, that are commonly used for pan-frying salmon, were chosen to test antioxidant capacity [30,40,41,42,43,44,45]. Rosemary showed the highest lipophilic antioxidant capacity (Figure 1A) and phenolic compound levels (Figure 1B), while black pepper had the highest hydrophilic antioxidant capacity and the second highest phenolic compound content.…”
Section: Resultsmentioning
confidence: 99%
“…Six condiments, that are commonly used for pan-frying salmon, were chosen to test antioxidant capacity [30,40,41,42,43,44,45]. Rosemary showed the highest lipophilic antioxidant capacity (Figure 1A) and phenolic compound levels (Figure 1B), while black pepper had the highest hydrophilic antioxidant capacity and the second highest phenolic compound content.…”
Section: Resultsmentioning
confidence: 99%
“…It was noted that lysozyme at low concentration (0.1% to 0.7%) exhibited excellent antimicrobial properties. Tural and Turhan (2017) investigated the effects of anchovy by-product protein added with thyme essential oil (1.5%) on shelf life of anchovy fillets. The application of protein-essential oil mixture as a coating agent reduced the total viable count, while no significant growth was observed in psychrotrophic counts between coated and uncoated groups.…”
Section: Animal Sourcementioning
confidence: 99%
“…Dried anchovy fish skins (500 g) were powdered via a blender (Model SHB 3062; Sinbo, Istanbul, Turkey). Powders of dried European anchovy fish skins (500 g) were hydrodistilled via a Clevenger-type device (Sesim Kimya Laboratuvar, Ankara, Turkey) by using 980 mL distilled water and 20 mL hydrochloric acid (37%) for 4 h according to modified method of Tural and Turhan [5].…”
Section: Instruments and Analysismentioning
confidence: 99%
“…As microorganisms grow, they produce nutrients and metabolites such as sulfuric compounds, aldehydes, ketones, esters, trimethylamine and the total volatile base nitrogen [3]. Previous studies reported an increase in protein and relative RNA content of anchovy, a decrease in carbohydrate and relative lipid content of anchovy as the anchovy larvae was growing [4,5]. In another study, silver ion high-performance liquid chromatography was used to examine the diversity and variations of the molecular triglyceride species derived from fish oils extracted from the laboratory [6].…”
Section: Introductionmentioning
confidence: 99%